PENGARUH PENDIDIKAN DAN PELATIHAN PENGUATAN KEPALA SEKOLAH DAN IKLIM SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR KECAMATAN WINONG - Kaswi; Gunawan Setiadi; Su`ad (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the low performance of teachers due to the lack of education and training to strengthen school principals and the lack of maintaining the school climate. The problems in this research were: 1) the influence of education and training to strengthen school principals on teachers' performance at Public Elementary Schools in Kecamatan Winong, Kabupaten Pati, 2) the influence of school climate on teachers' performance at Public Elementary Schools in Kecamatan Winong, Kabupaten Pati, 3) the influence of education and training to strengthen school principals and school climate to affect the teachers' performance at Public Elementary Schools in Kecamatan Winong, Kabupaten Pati. This research was quantitative research with a correlational study that sought for the influence between the independent variables of education and school principal strengthening training (X1) and school climate (X2), with the dependent variable: teachers' performance (Y). This research was conducted from July to August 2020 at 40 Public Elementary Schools in Kecamatan Winong. The total population was 267 and 160 samples were randomly selected. The data were collected through a questionnaire. The requirements tests used were the normality test, homogeneity test, linearity test, and multicollinearity test. The research plan was tested by using simple linear regression analysis, t-test, multiple linear regression analysis processed using the SPSS program. The result found that the data were normally distributed, homogeneous, linear, and not multicollinear. Then, the result of the hypothesis test found: 1) there was a relationship between the variable X1 and X2 with the equation of Y = 71.661 + 0.632X1; thus, the hypothesis was accepted. This means that every increase in education and strengthening training for principals increased teachers' performance by 0.632 at a constant of 71.661. The strength of the correlation was 0.685. The amount of contribution of variable X1 to Y equals 89.6%; 2) there was a relationship between variable X2 and Y with the equation of Y = 71.661 + 0.495X2. The strength of the correlation was 0.697 with a contribution of 74.4%; 3) there was a positive relationship between education and training to strengthen principals and school climate on teachers' performance which was expressed by the equation of Y = 71.661 + 0.632X1 + 0.495X2. The correlation score was 0.707. The contribution of variables X1 and X2 to Y was 79.6%, while 20.4% was influenced by other factors.